Discussion: Effect of Corrugated Roughness on Developed Laminar Flow in Microtubes, (Duan, Z. and Muzychka, y. M., 2008 Asme Trans. J. Fluids Eng., 130 P. 031102 - Siginer, D (2012)
Fully developed continuum flow through corrugated tubes with slip at the boundary is solved by perturbations and the results are compared with the work of Duan and Muzychka (Duan and Muzychka, 2008, Effects of Corrugated Roughness on Developed Laminar Flow in Microtubes, ASME Trans. J. Fluids Eng., 130, p. 031102). This note brings out and corrects the errata and extends the results obtained. © 2012 American Society of Mechanical Engineers.